Plasma electrolyte and hematological changes after marathon running in adolescents - Traiperm, N.; Gatterer, H.; Burtscher, M. (Medicine & Science in Sports & Exercise, 2013)
Purpose: The objective of this research is to study plasma electrolyte and hematological changes in adolescent runners completing a standard 42.2-km marathon run.